Perempuan Dan Pemahaman Agama (Refleksitentang Pemahamanagama Dalam Konteks Ketidakadilan Pada Perempuan): Women And Religious Understanding (Reflections On Religious Understanding In The Context Of Injustice Against Women) - Hanifah el Adiba (An-Nisa’ Journal of Gender Studies, 2010)
Since its emergence, Islam has truly been fully committed to elevating the status and dignity of women. In line with its historical development, Islam and its teachings have been interpreted in various ways according to the epistemological frameworks of the scholars who interpret and explain these teachings. This has led to diverse interpretations of women, as if women were worthless. This paper is an attempt to examine the normative arguments that have long been the basis for the recognition and justice for women. More than that, this paper is intended to send a signal that the commitment to the elevation of the dignity and status of women has existed. A reflective study was conducted based on several data and notes that the author found in the field. The data and notes were collected through interviews with. Sejak kemunculannya Islam sesungguhnya telah memberikan komitmen yang utuh bagi pengangkatan harkat dan martabat perempuan. Sejalan dengan bentangan historisitasnya, Islam dan ajarannya lalu dimaknai secara beragam sesuai dengan corak bangunan epistemologis masing-masing ulama pemberi makna dan penafsir ajaran itu. Hal ini menghadirkan konsekwensi pada apresiasi yang beragam pula terhadap perempuan dan seolah perempuan menjadi tidak berharga. Tulisan ini merupakan sebentuk upaya untuk melakukan telaah terhadap dalil-dalil normatif yang selama ini menjadi dasar dari pengakuan dan keadilan bagi perempuan. Lebih dari itu tulisan ini dimaksudkan untuk menghadirkan signal bahwa komitmen atas pengangkatan harkat dan martabat wanita itu pernah ada. Kajian reflektif dilakukan berdasarkan beberapa datum dan catatan pendampingan yang penulis temukan di lapangan.